Formal Concept Analysis 8th International Conference, ICFCA 2010, Agadir, Morocco, March 15-18, 2010, Procedings - Kwuida, Léonard; Sertkaya, Baris (Lecture Notes in Artificial Intelligence, 2010)
This volume contains selected papers presented at ICFCA 2010, the 8th Int- national Conference on Formal Concept Analysis. The ICFCA conference series aims to be the prime forum for dissemination of advances in applied lattice and order theory, and in particular advances in theory and applications of Formal Concept Analysis. Formal Concept Analysis (FCA) is a ?eld of applied mathematics with its mathematical root in order theory, in particular the theory of complete lattices. Researchershadlongbeenawareofthefactthatthese?eldshavemanypotential applications.FCAemergedinthe1980sfrome?ortstorestructurelattice theory to promote better communication between lattice theorists and potential users of lattice theory. The key theme was the mathematical formalization of c- cept and conceptual hierarchy. Since then, the ?eld has developed into a growing research area in its own right with a thriving theoretical community and an - creasingnumberofapplicationsindataandknowledgeprocessingincludingdata visualization, information retrieval, machine learning, sofware engineering, data analysis, data mining in Web 2.0, analysis of social networks, concept graphs, contextual logic and description logics. ICFCA 2010 took place during March 15-18, 2010 in Agadir, Morocco. We received 37 high-quality submissions out of which 17 were chosen as regular papers in these proceedings after a competitive selection process. Less mature works that were still considered valuable for discussion at the conference were collected in the supplementary proceedings. The papers in the present volume coveradvancesinvariousaspectsofFCArangingfromitstheoreticalfoundations to its applications in numerous other ?elds. In addition to the regular papers, thisvolumealsocontainsfourkeynotepapersarisingfromtheseveninvitedtalks given at the conference. We are also delighted to include a reprint of Bernhard Ganter'sseminalpaper on hiswell-knownalgorithmfor enumerating closedsets.